Influence of Replacement of Cotton Seed Cake with Ambadi Cake (Hibiscus canabinus L.) in the Diets of Indian Camels (Camelus dromedarius) - Gupta, Lokesh; Tiwari, G.S.; Garg, Rajeev (Indian Journal of Animal Nutrition, 2018)
The present study was undertaken to investigate the effect of replacement of cotton seed cake with ambadi cake (Hibiscus canabinus L.) on the performance of Indian camels. The experiment was carried out in 3 Ã— 3 latin square design using 3 treatments viz., T1: concentrate mixture using cotton seed cake; T2: 50%replacement of cotton seed cake by ambadi cake (Hibiscus canabinus L.) and T3: 100% replacement of cotton seed cake by ambadi cake in concentrate mixture. Iso-nitrogenous and iso-caloric concentrate mixtures were prepared. There was no significant difference in digestibility of nutrients. The DE and ME contents were 2.83 and 2.29, 2.88 and 2.32 and 2.74 and 2.21 Mcal/kg DM in treatments T1, T2 and T3, respectively. The dry matterand nutrient intakes were not affected by treatments on feeding ambadi cake at 16% level in concentrate mixture. There was also no significant difference for draught, speed of operation and power out on replacing conventional protein source with ambadi cake. Likewise, rectal temperature, pulse rate and respiration rate werealso similar in all the treatments but there was increase in the physiological responses in camels before and after carting irrespective of treatments. Thus, feeding of ambadi cake at 16% level in the concentrate mixture could safely replace cotton seed cake without affecting the performance of Indian camels under sustained working conditions.